Regulation of yeast RAD9 gene in energy charge, intracellular ROS, and cell cycle arrest in response to DNA damage - Ngoc, Bui Van; Hoa, Le Thanh (Vietnam Journal of Biotechnology, 2024)
In various environmental conditions, eukaryotic cells are exposed to many kinds of exogenous toxic agents as well as to endogenous agents like reactive oxygen species (ROS) generated from oxidative metabolism that can all result in damage to DNA. To cope with these types of damage, yeast cells have evolved a number of mechanisms and specific response systems regulated by key control genes. One of which is RAD9 gene that regulates DNA damage and repair checkpoints, and cell cycle arrest. Thus, a series of methods, e.g. oxygen consumption monitoring, physicochemical analysis, and flow cytometry, were used in the present study to investigate the role of the RAD9 gene by using the BY4742 (wild type) and specific knock-out yeast strains (∆rad9) and elucidate the function of this gene in cellular defense mechanism and metabolic response to DNA damage triggered by methyl methanesulfonate (MMS) treatment. The results indicated that fully functional DNA damage repair and cell cycle checkpoint (RAD9, wild type) significantly enhanced mitochondrial activity and oxygen consumption, reduced intracellular ROS accumulation. Fully functional mitochondria attenuated ROS accumulation, enabled efficient mitochondrial electron transport chain (mtETC) and ATP synthesis, and stabilized cellular energy status. Also, high mitochondrial activity acted as a protective mechanism against oxidative stress. In contrast, deletion of the RAD9 (∆rad9) resulted in high ROS accumulation and damaged to mitochondrial DNA, leading to strong inhibition of mitochondrial activity and oxygen consumption. Furthermore, low mitochondrial activity in cells lacking RAD9 (∆rad9) led to the development of oxidative stress. Subsequently, high ROS accumulation in ∆rad9 cells caused a block of the mtETC, repression of ATP synthesis, fluctuation of cellular energy status, and induction of cell cycle arrest at S and G2/M phases.